2015
DOI: 10.1007/s10640-015-9956-3
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and Competition in Climate Change Policies: Mitigation and Climate Engineering when Countries are Asymmetric

Abstract: We study a dynamic game of climate policy design in terms of emissions and solar radiation management (SRM) involving two heterogeneous regions or countries. Countries emit greenhouse gasses (GHGs), and can block incoming radiation by unilateral SRM activities, thus reducing global temperature.Heterogeneity is modelled in terms of the social cost of SRM, the environmental damages due to global warming, the productivity of emissions in terms of generating private bene…ts, the rate of impatience, and the private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…Recent study on the climate policy design in terms of emissions and solar radiation has suggested evaluating in terms of social cost and environmental changes. The impact of asymmetry on mitigation and solar radiation management has been found significant, and asymmetries play an important role in influencing incentives for cooperation and unilateral actions (Manoussi and Xepapadeas, 2017). Climate change in a political system of governance depends on national level public bureaucracies in order to formulate and implement effective and efficient measures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Recent study on the climate policy design in terms of emissions and solar radiation has suggested evaluating in terms of social cost and environmental changes. The impact of asymmetry on mitigation and solar radiation management has been found significant, and asymmetries play an important role in influencing incentives for cooperation and unilateral actions (Manoussi and Xepapadeas, 2017). Climate change in a political system of governance depends on national level public bureaucracies in order to formulate and implement effective and efficient measures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Second, CE deployment fits well into the public good structure: Deployment costs are borne by the deploying country alone while the effect of reduced GHG levels and temperatures is inevitably global. Finally, and central in this paper, countries differ in their assessment of an 'optimal climate' (Rosenzweig and Parry 1994;Porter et al 2014;Manoussi and Xepapadeas 2015;Heyen et al 2015); as a consequence, the assumption of heterogeneous preferences for deployment of the technology is particularly reasonable here.…”
Section: The Modelmentioning
confidence: 99%
“…Finally, this paper adds to the literature on the economics of CE with contributions focusing either on intergenerational heterogeneity (Goeschl et al 2013) or heterogeneity across countries (Moreno-Cruz 2010;Manoussi and Xepapadeas 2015). Most of these papers however are interested in the interplay of SRM with abatement from which the present study abstracts.…”
Section: Introductionmentioning
confidence: 99%
“…We develop a dynamic model of strategic interaction between two countries diverging in their perception of geoengineering and production possibilities. The model structure is similar to the asymmetric transboundary pollution game with a geoengineering option in Manoussi and Xepapadeas [14]. The difference is that we study a fully asymmetric trade game, in the sense of entirely different objectives for each country instead of different parameter values only.…”
Section: Introductionmentioning
confidence: 99%